2016
DOI: 10.3892/ol.2016.4140
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and systemic plasmacytosis on the face: Effective treatment of a case using thalidomide

Abstract: Abstract. Cutaneous and systemic plasmacytosis is an exceedingly rare condition that is identified in Japanese individuals in particular. The present study describes the case of a patient of mainland Chinese origin who manifested with red-brown macules, papules and plaques limited to the face. Identifying a therapy for cutaneous and systemic plasmacytosis is quite difficult, however, the present patient showed a good response to low-dose thalidomide. The exact mechanism of action is not yet clear, however, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Treatment with various calcineurin inhibitors has shown limited efficacy, and other interventions such as radiotherapy and photodynamic therapy have also been used. Other cases' reports describe reduction of lesions with chemotherapeutic drugs such as cyclophosphamide or vincristine, and one case of successful treatment with thalidomide has been reported 13 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment with various calcineurin inhibitors has shown limited efficacy, and other interventions such as radiotherapy and photodynamic therapy have also been used. Other cases' reports describe reduction of lesions with chemotherapeutic drugs such as cyclophosphamide or vincristine, and one case of successful treatment with thalidomide has been reported 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Recent reports of low-dose thalidomide, narrowband ultraviolet B therapy, mask-bath psoralen combined with ultraviolet A, and intralesional corticosteroid injections have shown improvement in cutaneous plasmacytosis. 13 , 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Data important to the diagnosis of cutaneous plasmacytosis include the percentage of IgG4 cells and IgG4 cells per high-power field (HPF). Detecting >200 IgG4+ plasma cells/HPF in the skin [15] or exceeding 40% of IgG4/IgG cells and >10 IgG4+ plasma cells/ HPF is mandatory for making a histological diagnosis of IgG4-RD [17] . Table 2 also shows the percentages of CD138, CD3, CD20, and the presence or absence of lightchain restriction, other helpful markers of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent case of cutaneous and systemic plasmacytosis, a 50-yearold woman from Mainland China with lesions limited to her face was successfully treated with thalidomide [15] . Fang et al [15] reported that the thalidomide may have decreased the secretion of interleukin-6 and thus affected plasma cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation